PREVALENCE AND PREDICTORS OF HYPOTENSION IN NURSING HOME RESIDENTS UNDERGOING AMBULATORY BLOOD PRESSURE MONITORING. (April 2021) - Rivasi, Giulia; Tortu', Virginia; D'Andria, Maria Flora; Turrin, Giada; Giuliani, Evelina; Ceolin, Ludovica; Rafanelli, Martina; Mossello, Enrico; Ungar, Andrea
Abstract : Objective: In nursing home (NH) residents, hypotension may predispose to adverse events including falls, fractures and mortality. Yet, evidence on hypotension detected by ambulatory blood pressure monitoring (ABPM) is scarce in this setting. This study aimed to determine the prevalence and the clinical predictors of ambulatory hypotension in NH residents and to analyze its related ABPM profile. Design and method: We retrospectively analysed data from a sample of 100 NH residents undergoing a comprehensive geriatric assessment and ABPM. Ambulatory hypotension was defined as a systolic blood pressure (SBP) drop of 20 mmHg or greater between two consecutive measurements to a minimum SBP < 100 mmHg. Participants with nocturnal hypotension were excluded from the analysis. Predictors of ambulatory hypotension were investigated using multivariate logistic regression adjusted for comorbidities, functional status and hypotensive medications. Results: Among 91 residents (mean age 83, 56% female), 50 showed ambulatory hypotension. They had a higher prevalence of heart failure (p = 0.02) and atrial fibrillation (p = 0.007) and more commonly received digoxin (p = 0.001) and benzodiazepines (p = 0.015). At ABPM they had lower 24 h, daytime and nighttime SBP (p < 0.001) and more frequently showed a white coat effect (p < 0.001) and a reverse-dipping profile (p = 0.013). At multivariate analysis, benzodiazepines (OR 4.040), digoxin (OR 19.987) and creatinine  < 1 mg/dl (OR 3.939) were independently associated with ambulatory hypotension. Conclusions: Hypotension is common in NH residents undergoing ABPM and more frequently occurs in subjects with lower ambulatory SBP, a reverse dipping profile and a white coat effect. Benzodiazepines, digoxin and low creatinine are predictors of ambulatory hypotension in NH residents.